PERSEPSI PEMILIH PEMULA DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR PROVINSI KALIMANTAN TENGAH TAHUN 2020 : (Studi di Kelurahan Muara Laung, Kecamatan Laung Tuhup, Kabupaten Murung Raya) - Muhamad Jordy; Jovano Deivid Oleyver Palenewen (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2021)
Perception is a process that is preceded by a sensing process, which is the process of receiving a stimulus by an individual through the senses or also called a sensory process. In this case in 2020, Laung Tuhup Subdistrict will take part in the Pilkada Simultaneously in the 2020 Central Kalimantan Governor and Deputy Governor Election. Therefore, conducting research on the Perceptions of Beginner Voters in the Election of Governor and Deputy Governor of Central Kalimantan Province is something that needs to be known in order to become a deep understanding. Beginner Voters' Perceptions. According to Robbin (2015), the theory used consists of perceptual indicators consisting of two indicators, namely judgment and evaluation. This research uses descriptive research method with a qualitative approach which is obtained based on the reasoning ability of researchers in connecting facts, data, and information recorded during the study. The research was conducted in Muara Laung, Laung Tuhup District, Murung Raya Regency, with members of PPS, PPK, and Beginner Voters. The data analysis used was data reduction, data presentation and conclusion drawing Based on the results of the research, related to the Perception of Beginner Voters in the Election of Gurnur and Deputy Governor of Central Kalimantan Province in 2020 in Muara Laung, Laung Tuhup District, Murung Raya Regency. which aims to determine the Perception of Beginner Voters in the Election for the Governor and Deputy Governor. Through acceptance and evaluation. Criminalization is a way for people to receive information and evaluation is a way for people to assess and filter information related to the election of governors and deputy governors. The supporting factor for perception is social media, while the inhibiting factor for perception is the lack of communication.